The Influence of Content Meaningfulness on Eye Movements across Tasks: Evidence from Scene Viewing and Reading - Luke, Steven G.; Henderson, John M. (Frontiers in Psychology, 2016)
The present study investigated the influence of content meaningfulness on eye-movement control in reading and scene viewing. Texts and scenes were manipulated to make them uninterpretable, and then eye-movements in reading and scene-viewing were compared to those in pseudo-reading and pseudo-scene viewing. Fixation durations and saccade amplitudes were greater for pseudo-stimuli. The effect of the removal of meaning was seen exclusively in the tail of the fixation duration distribution in both tasks, and the size of this effect was the same across tasks. These findings suggest that eye movements are controlled by a common mechanism in reading and scene viewing. They also indicate that not all eye movements are responsive to the meaningfulness of stimulus content. Implications for models of eye movement control are discussed.